Adoption of BARI Recommended Potato (Solanum tuberosum) Varieties by the Potato Farmers of Bangladesh (The Agriculturists, 2014)
This study was conducted to determine the extent of adoption of BARI recommended potato varieties by the potato growers in three Upazilas namely, Pirgachha of Rangpur, Munsiganj sadar of Munsiganj and Shibganj of Bogra district of Bangladesh. To achieve the objectives, the present research was designed to collect both qualitative and quantitative data. The study areas were selected purposively considering highly concentrated potato growing areas. Total numbers of potato growers in the selected areas were 581 from which 231 were selected as respondents following proportionate random sampling technique. A pre-tested interview schedule was used to collect data from the respondents during October, 2010 to February, 2011. The potato growers showed marked individual differences in their socio-economic characteristics and majority of them belonged to middle age category having small family size, primary level of education, small farm size, medium innovativeness and medium contact with extension personnel. The study revealed that the highest proportion (68.4%) of the potato farmers belonged to high adoption category; whereas 6.5 percent fall in medium adoption category and 25.1 percent in low adoption category of BARI recommended potato varieties. Extent of adoption of BARI recommended potato varieties were found more or less equal in three different study areas, where the highest (72.6%) portion of the potato farmers were in high adoption category in Munshiganj Sadar followed by 68.4 percent in Shibganj and 67.5 percent in Pirgachha. The studies also revealed that Diamant, Cardinal and Granola were the most popular varieties among all the released varieties of BARI and are largely grown in Munshiganj, Rangpur and Bogra, respectively. Farmers education and knowledge about potato cultivation technology showed significant positive relationship with their adoption of BARI recommended potato varieties. DOI: http://dx.doi.org/10.3329/agric.v11i2.17492 The Agriculturists 2013; 11(2) 79-86